2021
DOI: 10.1021/acsaelm.1c00288
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Range Epitaxial Strain Control of Electrical and Magnetic Properties in High-Quality SrRuO3 Films

Abstract: Epitaxial strain in 4d ferromagnet SrRuO3 films is directly linked to the physical properties through the strong coupling between lattices, electrons, and spins. It provides an excellent opportunity to tune the functionalities of SrRuO3 in electronic and spintronic devices. However, a thorough understanding of the epitaxial strain effect in SrRuO3 has remained elusive due to the lack of systematic studies. This study demonstrates widerange epitaxial strain control of electrical and magnetic properties in high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…The highest experimental RRR of 80.1, was achieved at the Ru flux = 0.365 Å/s, growth temperature = 826 °C, and O 3 -nozzle-to-substrate distance = 22 mm. This is the highest RRR ever reported among tensile-strained SrRuO 3 films 27,35 . The achievement of the target material with the highest conductivity in such a small number of optimizations demonstrates the effectiveness of this method utilizing the floor padding trick for high-throughput materials growth.…”
Section: Application For Ml-mbe Of Srruo 3 Filmsmentioning
confidence: 67%
See 2 more Smart Citations
“…The highest experimental RRR of 80.1, was achieved at the Ru flux = 0.365 Å/s, growth temperature = 826 °C, and O 3 -nozzle-to-substrate distance = 22 mm. This is the highest RRR ever reported among tensile-strained SrRuO 3 films 27,35 . The achievement of the target material with the highest conductivity in such a small number of optimizations demonstrates the effectiveness of this method utilizing the floor padding trick for high-throughput materials growth.…”
Section: Application For Ml-mbe Of Srruo 3 Filmsmentioning
confidence: 67%
“…We demonstrate the effectiveness of the BO method with experimental failure first by using virtual data for simulation, and subsequently through implementation for real materials growth, namely machine-learning-assisted molecular beam epitaxy (ML-MBE) of itinerant ferromagnetic perovskite SrRuO 3 thin films, where we used the residual resistivity ratio (RRR) as the evaluation value. We achieved the RRR of 80.1, the highest ever reported among tensile-strained SrRuO 3 films, through the exploitation and exploration in a wide three-dimensional parameter space in only 35 MBE growth runs-the tensile-strained SrRuO 3 thin films achieved by epitaxial strain showed higher Curie temperature than those of bulk or compressive-strained films 27 . The proposed method provides a flexible optimization algorithm for a wide multi-dimensional parameter space that assumes experimental failure, and it will enhance the efficiency of high-throughput materials growth and autonomous materials growth.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…43−46 This general tendency might be understood crudely by a simple picture that the overlap between the free electron wave functions becomes reduced with a larger lattice constant. 22 To understand how the local infrared conductivity varies near a nanocrack, we obtain e xx and S 2 values for a given distance from the nanocrack. Then, we plot these values as open circles in Figure 6b.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, VO 2 films were grown on conducting oxide SrRuO 3 (SRO) layers. Besides applications in magnetism, SRO is a widely studied template material to create multi-functional oxide heterostructures [34][35][36]. Furthermore, a recent simulation study has suggested that VO 2 /SRO bilayer heterostructures could be a promising candidate for relaxation oscillators [37].…”
Section: Experimental 21 Choice Of Substratementioning
confidence: 99%